Synthesis, structure, and hydrogen sorption properties of the Nd0.5Pr0.5MgNi4–xFex and Nd0.5Pr0.5MgNi4–xCux (x  0.5, 1, 2) alloys - Verbovytskyy, Yu.V.; Zavaliy, I.Yu.; Lyutyy, P.Ya.; Berezovets, V.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
New Nd0,5Pr0,5MgNi4–x(Fe, Cu)x (x  0.5, 1, 2) alloys are synthesized by the sintering method and characterized by the X-ray powder diffraction method. The crystal structure and hydrogen sorption properties are studied for some of them. Three hydrides with orthorhombic structure are prepared. Electrode materials for all alloys were made, and their main electrochemical characteristics (maximum discharge capacity and cyclic stability) were established. Additionally, obtained results are compared with related compounds of the composition Nd0,5Pr0,5MgNi4–xCox and discussed.